Extracellular vesicles from immortalized mesenchymal stromal cells protect against neonatal hypoxic-ischemic brain injury - Nicole Labusek; Yanis Mouloud; Christian Köster; Eva Diesterbeck; Tobias Tertel; Constanze Wiek; Helmut Hanenberg; Peter A. Horn; Ursula Felderhoff-Müser; Ivo Bendix; Bernd Giebel; Josephine Herz (BMC, 2023)
Abstract Background Human mesenchymal stromal cell (MSC)-derived extracellular vesicles (EV) revealed neuroprotective potentials in various brain injury models, including neonatal encephalopathy caused by hypoxia-ischemia (HI). However, for clinical translation of an MSC-EV therapy, scaled manufacturing strategies are required, which is challenging with primary MSCs due to inter- and intra-donor heterogeneities. Therefore, we established a clonally expanded and immortalized human MSC line (ciMSC) and compared the neuroprotective potential of their EVs with EVs from primary MSCs in a murine model of HI-induced brain injury. In vivo activities of ciMSC-EVs were comprehensively characterized according to their proposed multimodal mechanisms of action. Methods Nine-day-old C57BL/6 mice were exposed to HI followed by repetitive intranasal delivery of primary MSC-EVs or ciMSC-EVs 1, 3, and 5 days after HI. Sham-operated animals served as healthy controls. To compare neuroprotective effects of both EV preparations, total and regional brain atrophy was assessed by cresyl-violet-staining 7 days after HI. Immunohistochemistry, western blot, and real-time PCR were performed to investigate neuroinflammatory and regenerative processes. The amount of peripheral inflammatory mediators was evaluated by multiplex analyses in serum samples. Results Intranasal delivery of ciMSC-EVs and primary MSC-EVs comparably protected neonatal mice from HI-induced brain tissue atrophy. Mechanistically, ciMSC-EV application reduced microglia activation and astrogliosis, endothelial activation, and leukocyte infiltration. These effects were associated with a downregulation of the pro-inflammatory cytokine IL-1 beta and an elevated expression of the anti-inflammatory cytokines IL-4 and TGF-beta in the brain, while concentrations of cytokines in the peripheral blood were not affected. ciMSC-EV-mediated anti-inflammatory effects in the brain were accompanied by an increased neural progenitor and endothelial cell proliferation, oligodendrocyte maturation, and neurotrophic growth factor expression. Conclusion Our data demonstrate that ciMSC-EVs conserve neuroprotective effects of primary MSC-EVs via inhibition of neuroinflammation and promotion of neuroregeneration. Since ciMSCs can overcome challenges associated with MSC heterogeneity, they appear as an ideal cell source for the scaled manufacturing of EV-based therapeutics to treat neonatal and possibly also adult brain injury.